2018
DOI: 10.1007/s12028-017-0485-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Coagulopathy and Platelet Dysfunction to Transfusion Needs After Traumatic Brain Injury

Abstract: Patients presenting with penetrating TBI demonstrated increased coagulopathy compared to those with blunt TBI as measured by TEG and need for transfusion. PFA results did not correlate with TEG findings in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Patients with penetrating TBI were more hypocoagulable than patients with blunt TBI demonstrating a longer K-time and an abnormally low MA—findings consistent with clinical observations ( Fig. 2 E ) ( 38 , 40 ). Alpha angle was also lower in penetrating TBI patients but was still well above normal indicating normal clot propagation.…”
Section: Resultssupporting
confidence: 85%
“…Patients with penetrating TBI were more hypocoagulable than patients with blunt TBI demonstrating a longer K-time and an abnormally low MA—findings consistent with clinical observations ( Fig. 2 E ) ( 38 , 40 ). Alpha angle was also lower in penetrating TBI patients but was still well above normal indicating normal clot propagation.…”
Section: Resultssupporting
confidence: 85%
“…Previous studies have demonstrated a lack of correlation between the TEG parameter for platelet contribution to clot (MA or MCF) and VerifyNow testing. 31 Viscoelastic tests tend to utilize agonists other than ADP and AA, such as tissue factor and thromboplastin, and therefore compensate for isolation platelet dysfunction via other pathways. In this study, though a difference was observed in the ability of ADP to induce platelet aggregability when MVs from TBI blood were added to normal blood, the percent of platelet contribution to maximum clot firmness was not impacted.…”
Section: Discussionmentioning
confidence: 99%
“…For example, because of the nature of ex vivo aggregometry assays (lack of endothelium, lack of flow, and exogenous agonist stimulation of platelets), it remains unclear where impaired postinjury platelet aggregation lies on the spectrum of adaptive to maladaptive responses to injury. It should not be ignored that the majority of investigations in this area have relied on point‐of‐care platelet function assays that were intended to assess the effects of antiplatelet medication on platelet inhibition, and it is of concern that viscoelastic assays do not always correlate well with point‐of‐care assessment of platelet function in trauma patients . In fact, unpublished work by the authors of this review, using multiple electrode aggregometry, has shown identified that platelets may be endogenously activated by injury, diminishing their aggregation response to exogenous agonists.…”
Section: Mechanisms and Mediatorsmentioning
confidence: 99%